Production of English finite verb morphology: a comparison of SLI and mild-moderate hearing impairment. - Norbury, Courtenay Frazier; Bishop, Dorothy V. M.; Briscoe, Josie (Journal of Speech, Language & Hearing Research, 2001)
The performance on production of finite verb morphology of 19 children (ages 5;9-10;7) with mild-moderate sensorineural hearing impairment (SNH) was compared with that of 14 children with specific language impairment (SLI) (ages 7;2-10;9) and age-matched and language-matched control groups. On average, the SNH group outperformed the SLI group and was comparable to controls. However, a subset of the SNH group (n = 6) was impaired on one or both of these tasks. Degree of hearing loss or age of receiving hearing aids was not directly related to performance, but other language measures were. The subset was also significantly younger than the rest of the SNH group, suggesting that acquisition of finite verb morphology may be delayed in children with hearing impairments. Verb regularity had no effect on performance of any group, but word frequency and phonological complexity did exert an influence. The findings are discussed in relation to causative theories of SLI. Reprinted by permission of the publisher.